Mapping Your World with Community Analyst: An Easy to Use Tool to Map the Characteristics of U.S. Communities - Robert Swett; Lisa Krimsky (EDIS, 2014)
In recent years, the number of mapping and geospatial tools that are both feature-rich and easy to use has increased. This is good news because it allows many more of us to capitalize on the power and unique insights that such tools can provide without having to spend inordinate amounts of time learning how to use them. This article presents Community Analyst, a web application that provides access to thousands of business, demographic, economic, education, and health data variables for the United States. The application’s extensive suite of data metrics, in conjunction with on-demand reports and interactive color-coded maps, allows one to quickly explore the characteristics of one or more geographic areas. This 9-page fact sheet was written by Robert Swett and Lisa Krimsky, and published by the UF Department of School of Forest Resources and Conservation, October 2013.